20-Hydroxyeicosatetraenoic Acid (20-HETE) Modulates Canonical Transient Receptor Potential-6 (TRPC6) Channels in Podocytes - Roshanravan, Hila; Kim, Eun Y.; Dryer, Stuart E. (Frontiers in Physiology, 2016)
The arachidonic acid metabolite 20-hydroxyeicosatetraenoic acid (20-HETE) regulates renal function, including changes in glomerular function evoked during tubuloglomerular feedback (TGF). This study describes the cellular actions of 20-HETE on cultured podocytes, assessed by whole-cell recordings from cultured podocytes combined with pharmacological and cell-biological manipulations of cells. Bath superfusion of 20-HETE activates cationic currents that are blocked by the pan-TRP blocker SKF-96365 and by 50 μM La3+, and which are attenuated after siRNA knockdown of TRPC6 subunits. Similar currents are evoked by a membrane-permeable analog of diacylgycerol (OAG), but OAG does not occlude responses to maximally-activating concentrations of 20-HETE (20 μM). Exposure to 20-HETE also increased steady-state surface abundance of TRPC6 subunits in podocytes as assessed by cell-surface biotinylation assays, and increased cytosolic concentrations of reactive oxygen species (ROS). TRPC6 activation by 20-HETE was eliminated in cells pretreated with TEMPOL, a membrane-permeable superoxide dismutase mimic. Activation of TRPC6 by 20-HETE was also blocked when whole-cell recording pipettes contained GDP-βS, indicating a role for either small or heterotrimeric G proteins in the transduction cascade. Responses to 20-HETE were eliminated by siRNA knockdown of podocin, a protein that organizes NADPH oxidase complexes with TRPC6 subunits in this cell type. In summary, modulation of ionic channels in podocytes may contribute to glomerular actions of 20-HETE.